Investigator’s Personality as a Problem of Legal Psychology - V. S. Medvediev (Law and Safety)
The author of the article has revealed own position regarding the psychology of an investigator’s personality on the basis of the modified organizational and activity concept of a law enforcement officer’s personality, developed by A. M. Stolyarenko. It has been emphasized that the organizational and activity concept of an investigator’s personality was substantially developed and improved by national specialists in the field of legal psychology. It has been noted that there are a number of fundamental and applied researches of the personality’s professional genesis of the personnel of various services and units of the Internal Affairs Agencies and the National Police, its adaptability, reliability, competence, stress resistance, etc.